Metabolic Profile in a Cohort of Young Sicilian Patients with Klinefelter’s Syndrome: The Role of Irisin - Stefano Radellini; Valentina Guarnotta; Vincenzo Sciabica; Giuseppe Pizzolanti; Carla Giordano (International Journal of Endocrinology)
Klinefelter’s syndrome (KS) is the main cause of hypogonadism and infertility in men and is often related to obesity, metabolic syndrome, and diabetes. The purpose of our real-life observational study was to investigate the metabolic and anthropometric parameters in a population of patients with Klinefelter syndrome compared to a group of healthy age-matched subjects. Methods. In our study, 25 consecutive Caucasian adult outpatients (age range 21–52 years, mean age 32.9 ± 12.2) with KS in testosterone replacement therapy and 30 healthy men (age range 25–45 years, mean age 32.4 ± 7.62) were studied. In both groups of subjects, anthropometric indices, lipid profile, glucose metabolic parameters, HbA1c, the homeostasis model assessment estimate of HOMA-insulin resistance (IR), and the insulin sensitivity index (ISI) were evaluated. In addition, we assessed the complete hormonal gonadic status and irisin values in both groups of patients. Results. No significant differences were found in BMI and total blood testosterone levels between KS and control subjects. Patients with KS had significantly higher values of WC (p=0.028), HbA1c (p=0.018), HOMA-IR (p<0.001), FSH (p<0.001), LH (p<0.001), estradiol (p=0.001), and irisin (p=0.029) and significantly lower HDL-cholesterol (p=0.002), AMH (p<0.001), inhibin B (p<0.001), and ISI-Matsuda (p<0.001) compared to healthy controls. Univariate analysis revealed an inverse correlation between irisin and ISI-Matsuda (r = −0.128; p=0.010). These data were then confirmed in multivariate analysis. Conclusions. KS is characterized by early development of metabolic syndrome and in particular by alterations of the glucose metabolism, independently of testosterone levels serum and BMI. Irisin blood levels of Klinefelter’s patients are higher than in healthy subjects and positively correlate with the degree of insulin resistance.